Learning Satisfaction And Social Support In Relation To Academic Achievement - Syahputra, Andi; Basith, Abd; Abidah, Abidah; Ananda, Liasya Putri; Wei, Gao (JETL (Journal of Education, Teaching and Learning), 2024)
Academic achievement has been a crucial aspect in for the students to have a successful learning process. It requires learning satisfaction and social support in every learning step. This research aims to: 1) describe the level of learning satisfaction, social support, and academic achievement; 2) analyze the differences in learning satisfaction, social support, and academic achievement, and; 3) analyze the influence of learning satisfaction and social support on academic achievement. This research uses quantitative methods with a survey approach. The population is 430 students of the English department at Islamic Colleges in Aceh. The simple random sampling technique functions to take the sample of 239 students (43 male and 196 female students). The instruments used in data collection are the Learning Satisfaction Scale, Social Support Scale, and Great Point Academic documentation. The data analysis uses descriptive statistics, MANOVA, correlation, and Multiple Linear Regression. The results show that the learning satisfaction, social support, and academic achievement levels are in the high category. University differences affect learning satisfaction, social support, and academic achievement levels. Finally, learning satisfaction and social support have a simultaneous impact on academic achievement.